1996
DOI: 10.1046/j.1365-2648.1996.22012.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived professional support and the use of blocking behaviours by hospice nurses

Abstract: A prospective study of the impact of training 41 hospice nurses in assessment skills was used to test hypotheses that blocking behaviours would be used more when patients disclosed feelings and used less when nurses perceived that they had satisfactory professional support. Each nurse was asked to assess a patient's current problems before and after feedback training and 8 months later. Audiotape recordings of these interviews were rated by trained raters. They determined the frequency of nurses' responses whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 20 publications
5
72
0
3
Order By: Relevance
“…use of the newly acquired skills in practice, formed a barrier in putting the skills learned into practice; In this study, an overview is presented of fourteen Booth et al [19] reported that a positive work evaluation studies of communication training proenvironment led to increased use of facilitating grams for nurses. Most of the studies reviewed behaviours, which means the nurses ability to assess showed limited effects on nurses' behavioural and clarify patients' concerns.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…use of the newly acquired skills in practice, formed a barrier in putting the skills learned into practice; In this study, an overview is presented of fourteen Booth et al [19] reported that a positive work evaluation studies of communication training proenvironment led to increased use of facilitating grams for nurses. Most of the studies reviewed behaviours, which means the nurses ability to assess showed limited effects on nurses' behavioural and clarify patients' concerns.…”
Section: Discussionmentioning
confidence: 93%
“…In the study by Booth et al [19] and • It was published as a thesis or in a scientific Grond and Visser [9], it was reported that all ward journal.…”
Section: Communication Nonverbal Communication Refers Tomentioning
confidence: 99%
See 3 more Smart Citations